Perinatale Aspekte der SARS-CoV-2 Infektion - Longardt, Ann Carolin (Z Geburtshilfe Neonatol, 2020)
The novel coronavirus SARS-CoV-2 has developed into a pandemic, yet still has many unknowns. The modalities of transmission, different symptoms and manifestations as well as concomitant circumstances of the disease are insufficiently characterized. Especially patient groups in special situations like pregnant women and newborns have to be considered separately. The current knowledge about pregnancy, labor and the first days of life is characterized by particular uncertainty due to the scarce data available. However, there is currently no evidence of significant unfavorable maternal and perinatal outcome. Many pregnant women with SARS-CoV-2 infection remain asymptomatic. The possibility of vertical transmission to the child cannot be excluded with certainty. However, indications of vertical transmission were detected only in individual cases. Newborn infections are also rather rare, unspecific and usually mild, with respiratory symptoms dominating. In this article, the data available to date are examined in order to provide better information, advice and treatment for pregnant women and newborns with SARS-CoV-2 and to provide suggestions for future research.